Ohmic Heating for the dairy industry: a potential technology to develop probiotic dairy foods in association with modifications of whey protein structure - Pereira, Ricardo N. (2018)
The use of whey in dairy probiotics is a topic of great interest to the scientific community and the food industries. However, few studies address the effect of ohmic heating (OH) on cell metabolism and growth parameters of probiotic microorganisms. Despite of this, OH under sub-lethal conditions presents promising results regarding the enhancement of growth rate and bacteriocin activity, leading to considerable improvements in the fermentation process. Thus, this review highlights the main findings and advances on the effect of OH on probiotic metabolism, while addressing the modification of whey protein structure as potential carrier of probiotic entities, aiming at stimulating interest and encouraging the development of functional products using OH.